QOLP-24. ENGAGING PATIENTS AND CAREGIVERS TO IMPROVE THE IMPORTANCE AND QUALITY OF SUPPORTIVE CARE RESEARCH IN NEURO-ONCOLOGY. (9th November 2020) - Peters, Katherine; Randazzo, Dina; Johnson, Margaret; Kim, Jung-Young; Patel, Mallika; Affronti, Mary
Abstract: BACKGROUND: From the time of diagnosis to end of life, patients with primary brain tumors experience challenges to maintain quality of life. While traditional research focuses on clinical trials that involve directly treating cancer, we have designed a specific research committee at our institution that promotes supportive care research to improve patients' and caregivers' quality of life. Past research has shown that issues key to patients and caregivers often differ from what researchers and providers might appreciate as important. Incorporating input from brain tumor patients and caregivers is vital to direct the most relevant and necessary supportive care research. METHODS: As part of an IRB-approved quality improvement project, we sought the opinions of our supportive care research committee about what are the essential quality of life issues for brain tumor patients and caregivers. We polled our committee before and after a session with patients and caregivers discussing factors relevant to their quality of life. After this patient/caregiver intervention, we used a group discussion and note comparison technique to distill down key elements to advance supportive care research for this population. RESULTS: Engagement of the committee included members that were neuro-oncology providers, biostatisticians, and data/regulatory/clinical trial staff. Before the intervention, common themes about key issues for patients and caregivers were comfort, pain management, counteracting side effects, cognitive issues, and financial toxicity. While similar themes emerged after the patient/caregiver intervention, the committee gleaned that aspects of communicating outcomes and support of caregivers were consistently mentioned from the discussion session with patients and caregivers. CONCLUSIONS: Opinions of brain tumor patients and caregivers are crucial in driving future direction and relevance of supportive care research in neuro-oncology. Our supportive care research committee will continue to engage patients and caregivers and are planning interventions to improve communication and support for caregivers.